Degradation of imidacloprid by fluidized-bed Fenton process - Battung, Elaine Joy T.; De Luna, Mark Daniel G.; Lu, Ming-Chun (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Imidacloprid (IMD), C9H20CIN5O2, one of the most widely-used neonicotinoid pesticides, has been proven resistant to conventional treatment processes. The increase in its usage has led to a rise in its detection in surface waters, and along therewith is its adverse effects on non-target organisms. This research focuses on the use of Fenton's reagent in a fluidized bed reactor in degrading IMD. The effects of pH and Fenton's reagent concentration on the extent and kinetics of IMD degradation were determined. These parameters were optimized using response surface methodology (RSM). It was observed that increasing the H2O2 and Fe2+ concentrations up to certain values improved the removal efficiency of the system. The optimum pH was established to be around 2.8 to 3.0. The model equation for the extent of removal derived from RSM accurately predicted both the IMD removal and decrease in soluble iron concentration at the optimized conditions (H2O2 : IMD = 5.2:1; H2O2: Fe = 3.3:1). 98.8 % IMD removal was achieved after two hours. It was also found that IMD degradation followed first-order degradation kinetics. Furthermore, the removal efficiencies of the fluidized-bed Fenton system and conventional Fenton system were compared. Without the carriers, a decrease in the rate of reaction in the Fe3+/H2O2 stage was observed, which led to lower removal efficiency. This study shows that fluidized-bed Fenton process could be used to effectively treat IMD-contaminated waters.
Thesis (Master of Science in Environmental Engineering)--University of the Philippines Diliman
Keywords: Imidacloprid; Pesticides -- Biodegradation